HUBUNGAN DUKUNGAN SUAMI DENGAN TINGKAT KECEMASAN PADA IBU HAMIL PRIMIGRAVIDA DI PUSKESMAS PONTIANAK TIMUR - Popy, Popy; Fitriah, Fitriah; Meta Aldila Listiya (Journal of Innovation Research and Knowledge, 2025)
A first pregnancy is a crucial period for women, often leading to anxiety due to the uncertainty and physical and mental changes experienced. While husband support is crucial in helping pregnant women reduce anxiety, many women still experience high levels of anxiety due to a lack of emotional support, information, and practical assistance from their partners. The first pregnancy is a particularly sensitive period for anxiety. The husband's role in providing support significantly impacts a pregnant woman's ability to cope with her anxiety. The problem is that many pregnant women experience high levels of anxiety due to a lack of husband support. Therefore, the aim of this study was to understand the relationship between partner support and anxiety levels in primigravida pregnant women. This study employed a quantitative approach through a cross-sectional design. The sample consisted of 36 first-time pregnant women who met certain criteria and were selected using a total sampling technique. The results of the study indicate that the majority of respondents (55.6%) stated that their husbands did not provide support, while the majority of respondents (44.4%) experienced mild levels of anxiety. No respondents experienced high levels of anxiety. Spearman Rank analysis showed that a p-value of 0.00 indicates a significant relationship between husband's support and the level of anxiety of pregnant women. The correlation coefficient of 0.949 indicates a very strong relationship between husband's support and the level of anxiety in pregnant women. In other words, the greater the support received by the wife, the lower the level of anxiety in pregnant women. The results of this study indicate a relationship between husband's support and the level of anxiety in pregnant women experiencing their first pregnancy. It is hoped that husbands are able to provide both emotional and financial support to pregnant women